2022
DOI: 10.1021/acsaelm.2c00526
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Charge Injection on the Switching Speed of Ferroelectric Memory Based on HfO2

Abstract: Ferroelectric hafnium oxide films are attracting interest as a promising functional material for non-volatile ferroelectric memory due to a number of excellent advantages including perfect compatibility with Si technology, full scalability, low power consumption, high endurance, and a nanosecond switching speed. A high switching speed is inherent for all inorganic ferroelectrics, and it originates from the thermodynamics of polarization reversal. Another fundamental property of ferroelectric films is that the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 16 publications
1
5
0
Order By: Relevance
“…The authors also concluded that at low external field E position of Lorentzian distribution satisfies the following relation: where α is the activation field, i.e., the electric field that would cause immediate polarization switching. In previous work [ 4 ], we indeed obtained a linear dependence of t Lorentz on voltage in the range of small voltages, which is consistent with the results obtained in [ 22 ]. However, as can be seen from the plot in Figure 2 d, the dependence obtained in this work for wider range of voltage is more similar to that obtained using the classical distribution function (2) for the NLS model [ 8 ].…”
Section: Resultssupporting
confidence: 92%
See 4 more Smart Citations
“…The authors also concluded that at low external field E position of Lorentzian distribution satisfies the following relation: where α is the activation field, i.e., the electric field that would cause immediate polarization switching. In previous work [ 4 ], we indeed obtained a linear dependence of t Lorentz on voltage in the range of small voltages, which is consistent with the results obtained in [ 22 ]. However, as can be seen from the plot in Figure 2 d, the dependence obtained in this work for wider range of voltage is more similar to that obtained using the classical distribution function (2) for the NLS model [ 8 ].…”
Section: Resultssupporting
confidence: 92%
“…An alternative explanation of retardation behavior may come from charge injection and charge accumulation in the nearby-electrode passive layer of the ferroelectric film. During the long set pulse, due to field-induced charge injection, the built-in field emerges and increases with time, which causes the offset of applied voltage V appl and decrease in the real voltage V f right during the time of switching [ 4 ]. To calculate the instant real voltage V f , we numerically solved the following system of Equations (2)–(4): …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations